1993
DOI: 10.1897/1552-8618(1993)12[2097:tabosp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

TOXICITY AND BIOACCUMULATION OF SOIL PCBs IN CRICKETS: COMPARISON OF LABORATORY AND FIELD STUDIES

Abstract: Laboratory and field studies were used to investigate toxicity and bioaccumulation of PCBs in crickets exposed to contaminated soil A 14-d laboratory soil bioassay with the house cricket (Acheta domesticus) yielded an LC50 of 1,200 ppm Aroclor 1254 Mean whole body concentrations of Aroclor 1254 in exposed crickets were 1 I , 48, 92, 149, and 144 ppm for soil test concentrations of 100, 250, 500, 1,000, and 2,000 ppm, respectively A whole body concentration of about 150 pprn appears to be a threshold concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…We observed a large and significant decline in total microarthropod abundance between Aroclor 1254 concentrations of 500 and 2,500 g/g, suggesting that a toxic threshold for this PCB lies somewhere between these two concentrations. We believe our results provide the first information on the toxic effect of a PCB on soil microarthropods, and it is likely that the LC50 for microarthropods is similar to that observed for crickets [24]. Using a laboratory soil bioassay, Paine et al [24] determined an LC50 for crickets of 1,200 g/g for Aroclor 1254, and they concluded that a whole-body concentration of 150 g/g was the threshold at which acute mortality would be observed.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We observed a large and significant decline in total microarthropod abundance between Aroclor 1254 concentrations of 500 and 2,500 g/g, suggesting that a toxic threshold for this PCB lies somewhere between these two concentrations. We believe our results provide the first information on the toxic effect of a PCB on soil microarthropods, and it is likely that the LC50 for microarthropods is similar to that observed for crickets [24]. Using a laboratory soil bioassay, Paine et al [24] determined an LC50 for crickets of 1,200 g/g for Aroclor 1254, and they concluded that a whole-body concentration of 150 g/g was the threshold at which acute mortality would be observed.…”
Section: Discussionsupporting
confidence: 70%
“…We believe our results provide the first information on the toxic effect of a PCB on soil microarthropods, and it is likely that the LC50 for microarthropods is similar to that observed for crickets [24]. Using a laboratory soil bioassay, Paine et al [24] determined an LC50 for crickets of 1,200 g/g for Aroclor 1254, and they concluded that a whole-body concentration of 150 g/g was the threshold at which acute mortality would be observed. Earthworms are known to accumulate PCBs above levels in soil [25][26][27][28], but we are aware of only one study that determined toxic PCB levels for earthworms.…”
Section: Discussionsupporting
confidence: 70%
“…The presence of dioxins (polychlorinated biphenyls (PCBs)) and dioxin-like (DL-PCBs) in insects is an unexplored field. Paine et al (1993) studied the concentration of PCBs in reared crickets without direct contact with soil in a naturally PCB polluted environment. Results suggest that PCBs are quickly absorbed by crickets but not accumulated.…”
Section: 3mentioning
confidence: 99%
“…We observed a large and significant decline in total microarthropod abundance between Aroclor 1254 concentrations of 500 and 2,500 μg/g, suggesting that a toxic threshold for this PCB lies somewhere between these two concentrations. We believe our results provide the first information on the toxic effect of a PCB on soil microarthropods, and it is likely that the LC50 for microarthropods is similar to that observed for crickets [24]. Using a laboratory soil bioassay, Paine et al [24] determined an LC50 for crickets of 1,200 μg/g for Aroclor 1254, and they concluded that a whole‐body concentration of 150 μg/g was the threshold at which acute mortality would be observed.…”
Section: Discussionmentioning
confidence: 53%
“…We believe our results provide the first information on the toxic effect of a PCB on soil microarthropods, and it is likely that the LC50 for microarthropods is similar to that observed for crickets [24]. Using a laboratory soil bioassay, Paine et al [24] determined an LC50 for crickets of 1,200 μg/g for Aroclor 1254, and they concluded that a whole‐body concentration of 150 μg/g was the threshold at which acute mortality would be observed. Earthworms are known to accumulate PCBs above levels in soil [25–28], but we are aware of only one study that determined toxic PCB levels for earthworms.…”
Section: Discussionmentioning
confidence: 53%